Competency Certification and Environmental Education as Predictors of Hazardous Waste Compliance among FPSO Workers - Budiman Oenyi; Rinawati; Tugiono; Samsul Bakri; Gregorius Nugroho Susanto; Agafirdus Irvandus Blutuk (LPPM STIE KRAKATAU, 2026)
Hazardous waste management on Floating Production, Storage, And Offloading (FPSO) vessels is a critical issue owing to strict regulations, operational isolation, and limited storage capacity. This study examined whether demographic, human capital, and organizational factors influence employee compliance in FPSO in Indonesian waters. A cross-sectional survey and structured observation were conducted among 90 workers, and the data were analyzed using ordinal logistic regression. The results show that competency certification significantly predicts compliance (OR=0.06, p=0.044), while environmental education has a marginal effect (OR=0.10, p=0.086). The other factors were not significant. These findings indicate that certification and environmental learning are more influential than demographic or job-related factors are. This study contributes to the offshore Health, Safety, and Environment (HSE) literature by extending human capital theory on compliance behavior. Practically, this emphasizes the need to strengthen certification and environmental training. However, limitations include the single-site, cross-sectional design and potential response bias, which may limit generalizability.